Ecologia populacional de Campomanesia xanthocarpa O. Berg (Myrtaceae) - Almeida, Silvia Mara Zanela (2020)
The lack of information on the ecology of populations of native fruit trees, including guabirobeira, and the necessity to identify recovery and conservation strategies, requires the development of research that seeks knowledge about the ecology of species. Its conservation depends on the preservation of its habitat (in situ), on the cultivation by traditional farmers (on farm) and on the ex situ conservation. It is necessary to know if the guabirobeira is regenerating and under what conditions this regeneration is taking place. The present study aimed to verify the occurrence of natural regeneration of guabirobeira in two forest fragments, and for this, experiments of population ecology were conducted with the specific objectives of: analyzing the population structure, the pattern of spatial distribution and the demographics of the species; to verify the relationship between the regeneration of guabirobeiras and the canopy opening; to determine the phenological pattern of guabirobeira and to evaluating the estimated production of fruits and seeds. The study was accomplished in remaining forests of Mixed Ombrophilous Forest in Western Santa Catarina. Three sample units (SU) of 50 x 50 meters were demarcated and all individuals were measured in terms of total height (TH), diameter at ground height (DGH), diameter at chest height (DCH) and the Cartesian coordinates (X-axis and Y-axis) were obtained. The plots’ assessments were carried out annually in the period from 2016 to 2018. Demographic rates of the population were calculated, the characterization of the canopy opening, phenological monitoring and the monitoring of fruit and seed production were carried out. Through the results of the present study, it can be observed that the populations of guabirobeira in two sample units are growing and expanding, while in a third unit, it shows an indication of population decline and actions to mitigate this effect should be accomplished to increase the regeneration of the species in this area. Guabirobeiras exhibited seasonal and annual pattern of occurrence of vegetative and reproductive phenophases. Fruit maturation is uneven and lasts approximately 30 days in each guabirobeira. The rate of canopy opening did not interfere in the internal regeneration of each population. In the EUC (Eucalyptus) plot there was the largest number of regenerating individuals and the largest canopy opening, while the population of NAT2 (Native 2) had the smallest canopy opening, but the number of regenerating was higher than the NAT1 population (Native 1). This indicates that historical factors of anthropic management and/or natural and ecological disorders should have a greater influence than the opening of the canopy merely. The more open understory explains the greater number of regenerating individuals in EUC in relation to areas with native forest (NAT1 and NAT2). The higher production of fruits/seeds in NAT2 may explain the greater regeneration in this area in relation to NAT1.